Gravity Model Applications and Macroeconomic Perspectives - Jasmin Katrin Gröschl (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2013)
This dissertation was prepared by Jasmin Gröschl and is a collection of five self-contained empirical essays. They aim at contributing to the understanding of non-standard determinants of trade and migration: historical and cultural characteristics in the United States (Chapter 1), policy-induced regulations in agricultural and food products (Chapter 2), and natural disasters (Chapter 3); and how international integration of countries shapes economic growth and helps to contain the costs of natural disasters: trade openness and income per capita (Chapter 4), and natural disasters, international integration, and economic growth (Chapter 5).
Keywords: C23; C26; F14; F15; F22; F43; N72; N92; O15; O40; Q17; Q54; Z10; 330; American Secession; Intranational Trade; US State Level; Gravity; International Trade; Sanitary and Phytosanitary Measure; Natural Disaster; International Migration; Income Per Capita; Openness; Instrumental Variable; Institutions; Geography; Gravitationsmodell; Internationale Wirtschaftsbeziehungen; Internationale Migration; Katastrophe; Wirkungsanalyse